Effectiveness of Emo-Demo to Improve Knowledge and Skills in Stunting Prevention Behavior in Infants Aged 0–6 Months - Noviana, Ulva; Haris, Mustofa; Suryaningsh, Merlyna (Knowledge Dynamics, 2025)
Background: Stunting is a persistent malnutrition issue caused by prolonged inadequate nutritional intake. The results of the preliminary study that was conducted found low stunting prevention behavior in infants aged 0-6 months in Jaddih Village. The objective of the research was to evaluate the efficiency of the Emo-Demo method in improve knowledge and skills in stunting prevention behavior. Methods: The research design was quasi-experimental. The independent variables was health education with the Emo-Demo method, and the dependent variables were knowledge, skills, and behavior. This study used questionnaires and statistical tests including the Wilcoxon test, paired sample t-test, independent t-test, Spearman Rank, and linear regression. Results: The Wilcoxon test obtained p=0.000<0.05, indicating a difference in knowledge before and after the Emo-Demo intervention. The paired sample t-test obtained p=0.000<0.05, indicating a difference in knowledge before and after the lecture intervention. A p-value of 0.000<0.05 was found, indicating a difference in skills before and after the Emo-Demo intervention. However, p = 0.083 > 0.05 indicated no significant difference in skills before and after the lecture intervention. The independent t-test showed significant differences in knowledge (p = 0.022) and skills (p = 0.021) between treatment and control groups. Spearman Rank analysis revealed significant correlations between knowledge and behavior (p = 0.047, r = 0.354), and between skills and behavior (p = 0.004, r = 0.494). Combined, knowledge and skills significantly influenced behavior (p = 0.046). Conclusion: The Emo Demo method is effective and efficient in increasing knowledge, skills and behavior related to stunting prevention care. Health workers and service facility staff are expected to help reduce stunting prevalence by promoting maternal preventive behaviors for infants aged 0-6 months through health education using the Emo-Demo method.